SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT LEUKEMIA DENGAN METODE BACKWARD CHAINING - Nofriadi man; Elma wati; Rima Fitri Yeni (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2016)
Leukemia or blood cancer today is not detected early and the cause can not be in the unknown. The cost of examination and specialists who are sometimes not in place resulted in a lack of motivation of people to check early, when the cancer early checks can be dealt with quickly. To overcome this they invented an expert system that is created using the programming language Java, which can help experts in dealing with the diagnosis of leukemia using the method of inference Backward Chaining. The results of this design is a leukemia expert system applications, where users can check the program or examination and received the diagnosis of the disease suffered by the user program.Keywords : Expert System, Leukemia